Impact of National Lockdown on the Hyperacute Stroke Care and Rapid Transient Ischaemic Attack Outpatient Service in a Comprehensive Tertiary Stroke Centre During the COVID-19 Pandemic - D'Anna, Lucio; Brown, Maddison; Oishi, Sikdar; Ellis, Natalya; Brown, Zoe; Bentley, Paul; Drumm, Brian; Halse, Omid; Jamil, Sohaa; Jenkins, Harri; Malik, Abid; Kalladka, Dheeraj; et al. (Frontiers in Neurology, 2021)
Background: The COVID-19 pandemic is having major implications for stroke services worldwide. We aimed to study the impact of the national lockdown period during the COVID-19 outbreak on stroke and transient ischemic attack (TIA) care in London, UK. Methods: We retrospectively analyzed data from a quality improvement registry of consecutive patients presenting with acute ischemic stroke and TIA to the Stroke Department, Imperial College Health Care Trust London during the national lockdown period (between March 23rd and 30th June 2020). As controls, we evaluated the clinical reports and stroke quality metrics of patients presenting with stroke or TIA in the same period of 2019. Results: Between March 23rd and 30th June 2020, we documented a fall in the number of stroke admissions by 31.33% and of TIA outpatient referrals by 24.44% compared to the same period in 2019. During the lockdown, we observed a significant increase in symptom onset-to-door time in patients presenting with stroke (median = 240 vs. 160 min, p = 0.020) and TIA (median = 3 vs. 0 days, p = 0.002) and a significant reduction in the total number of patients thrombolysed [27 (11.49%) vs. 46 (16.25%, p = 0.030)]. Patients in the 2020 cohort presented with a lower median pre-stroke mRS (p = 0.015), but an increased NIHSS (p = 0.002). We registered a marked decrease in mimic diagnoses compared to the same period of 2019. Statistically significant differences were found between the COVID and pre-COVID cohorts in the time from onset to door (median 99 vs. 88 min, p = 0.026) and from onset to needle (median 148 vs. 126 min, p = 0.036) for thrombolysis whilst we did not observe any significant delay to reperfusion therapies (door-to-needle and door-to-groin puncture time). Conclusions: National lockdown in the UK due to the COVID-19 pandemic was associated with a significant decrease in acute stroke admission and TIA evaluations at our stroke center. Moreover, a lower proportion of acute stroke patients in the pandemic cohort benefited from reperfusion therapy. Further research is needed to evaluate the long-term effects of the pandemic on stroke care.